Comparative microbiological, chemical, and sensory traits of aron fermentation in Tengger and laboratory scales - Oki Krisbianto; Andre Yusuf Trisna Putra; Masdiana Chendrakasih Padaga; Hari Minantyo (AGROINTEK, 2024)
Aron, a traditional fermented food of the Tengger community, is made from white corn grown in Bromo and has received limited microbiological, chemical, and sensory research attention to date. The research objective was to compare microbiological, chemical, and sensory traits between in situ-produced aron on the slopes of Mount Bromo and ex situ-produced aron in a laboratory in Surabaya. A specific strain of lactic acid bacteria was isolated using de Man, Rogosa, and Sharpe (MRS) Agar from samples of sun-dried white corn. This strain was identified as Gram-positive cocci. In contrast, a different strain of Gram-positive bacilli was found in corn-soaking water, both in situ and in laboratory-fermented aron, on days 0, 7, and 16. Chemical analysis revealed no significant differences in protein, fat, and ash content between the two variables. However, laboratory-fermented aron exhibited higher moisture content. This discrepancy significantly influenced the hedonic texture data for aron, with in situ aron being perceived as drier and more mouth-soluble, while laboratory-fermented aron had a softer texture. Furthermore, the high microbial growth during the fermentation process resulted in aron with a distinct and relatively strong aroma that was less favored by the panelists. The difference in the fermentation location of white corn did not affect the types of lactic acid bacteria that thrived, the nutritional compound content, and the appearance of aron. The variation in the aroma of aron is believed to be primarily influenced by the number of bacteria rather than their specific strains.